(untitled) (Bangladesh Journal of Livestock Research, 2025)
The Special Efforts Program for Compulsory Pregnancy of Cattle and Buffalo (Upsus Siwab) and SIKOMANDAN (National Commodity Cattle and Buffalo) are strategic initiatives by the Indonesian Ministry of Agriculture aimed at boosting livestock populations through reproductive optimization. This study evaluates the impact of these programs on livestock reproductive performance and farmers’ economic conditions in Sorong Regency, Southwest Papua, by comparing data from 2017 to 2025. The results show that both programs significantly improved pregnancy rates, births, and farmers’ incomes compared to the national average. Projections to 2025 indicate a trend of sustained performance improvement and increasing cost efficiency. This article outlines the achievements, challenges, and strategies to enhance program success in the future. Bang. J. Livs. Res. Vol. 30 (1&2), 2023: P. 48-57